2009
DOI: 10.1104/pp.108.134536
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Closed Electrical Circuits in Venus Flytrap

Abstract: The Venus flytrap (Dionaea muscipula Ellis) is a marvel of plant electrical, mechanical, and biochemical engineering. The rapid closure of the Venus flytrap upper leaf in about 0.1 s is one of the fastest movements in the plant kingdom. We found earlier that the electrical stimulus between a midrib and a lobe closes the Venus flytrap upper leaf without mechanical stimulation of trigger hairs. The Venus flytrap can accumulate small subthreshold charges and, when the threshold value is reached, the trap closes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
60
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 25 publications
(12 reference statements)
1
60
1
Order By: Relevance
“…10 Some plants exhibit clues of an electrical memory as well. 1,2,7 We found that Venus flytrap has a short term electrical memory. 1,2,7 Rapid closure of the carnivorous plant Dionaea muscipula Ellis (Venus flytrap) has been attracting the attention of researchers and as a result its mechanism has been widely investigated.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…10 Some plants exhibit clues of an electrical memory as well. 1,2,7 We found that Venus flytrap has a short term electrical memory. 1,2,7 Rapid closure of the carnivorous plant Dionaea muscipula Ellis (Venus flytrap) has been attracting the attention of researchers and as a result its mechanism has been widely investigated.…”
mentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9] The existence of different forms of plant memory is well known. 7 Depending on the duration of memory retention, there are three types of memory in plants: sensory memory, short term memory and long term memory.…”
mentioning
confidence: 99%
“…1,3,29 Plants have a biological clock and circadian rhythms, which involve electrical elements of memory. 1,2,3,29 We should expect the finding of biomemristors in many different biological systems …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The standard electrical circuits comprise 3 basic elements: a resistor, a capacitor and an inductor. In addition to these elements, Chua,5 postulated the existence of a new element, which has electrical memory ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of electrophysiological mechanisms for information perception, transmission and processing between different plant organs and tissues, allowing the expression of fast and accurate physiological reactions to specific biotic or abiotic stimuli, is expressed by means of real-time detectable action (APs) and variation (VPs) potentials (Datta & Palit, 2004;Lautner et al, 2005;Oyarce & Gurovich, 2010;Volkov et al, 2009;Wang et al, 2009). An additional type of electric potential in plants has been proposed by Zimmermann et al (2009), to be called system potential.…”
Section: Introductionmentioning
confidence: 99%